1999
DOI: 10.1161/01.hyp.34.5.1047
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Leptin Level Is Associated With Myocardial Wall Thickness in Hypertensive Insulin-Resistant Men

Abstract: Abstract-Leptin, the product of the ob gene, has been shown to increase heart rate and blood pressure through a stimulation of cardiac sympathetic nervous system activity, a phenomenon also involved in the pathogenesis of left ventricular hypertrophy in hypertensives. Thus, we hypothesize that plasma leptin concentration is associated with left ventricular hypertrophy. Forty hypertensive males and 15 healthy male subjects underwent anthropometric and echocardiographic evaluations, assessment of insulin sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
90
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 38 publications
4
90
0
3
Order By: Relevance
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy. Furthermore, in patients with CAD16 and acute myocardial infarction,24 a positive association has been reported between circulating leptin levels and markers of LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similar to our observations, several population‐based studies, including MESA (Multi‐Ethnic Study of Atherosclerosis)10 and a previous study of elderly participants in the original cohort of FHS,29 have reported an inverse association between circulating leptin concentrations and LVM but no association with measures of LV systolic function 29. In contrast, other observational studies of men with hypertension,22 of severely obese patients23 and of patients with myocardial infarction24 have reported a positive association between leptin and cardiac hypertrophy. Furthermore, in patients with CAD16 and acute myocardial infarction,24 a positive association has been reported between circulating leptin levels and markers of LV diastolic dysfunction.…”
Section: Discussionsupporting
confidence: 88%
“…Accordingly, investigators have related circulating concentrations of adipokines to imaging indices of cardiac remodeling. These prior studies have typically been conducted in small samples, or samples with an overrepresentation of obese individuals or elderly people, and usually focused on a single adipokine 10, 11, 13, 21, 22, 23, 24, 25, 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in healthy individuals free from cardiovascular disease, Pladevall et al (28) showed that leptin deficiency was associated with increased left ventricular mass index, thus demonstrating that leptin has an antihypertrophic effect in the presence of an intact signaling pathway. Although some older studies showed a positive correlation between leptin and LVH when adjusting for body mass index (BMI) (29), others have highlighted that this positive correlation is completely abrogated after adjusting for BMI (30). Nonetheless, it is well established that obesity in clinical populations is associated with elevated leptin primarily due to leptin resistance, implying depressed downstream signaling despite increased leptin levels (4,8,9).…”
Section: Discussionmentioning
confidence: 99%
“…26 In vitro studies have demonstrated that leptin promotes angiogenesis 27 and induces oxidative stress in human endothelial cells. 28 Moreover, epidemiological studies have recently shown that leptin is independently associated with myocardial wall thickness in hypertensive insulin-resistant men, 29 is a risk factor for haemorrhagic stroke in a population-based cohort, 30 and is associated with increased risk of myocardial infarction. 31 Lastly, studies in animal models showed that leptin may have a pathophysiological role in obesity-related hypertension.…”
Section: Discussionmentioning
confidence: 99%